Analisis Perilaku Perawat Tentang Penggunaan Gelang Identifikasi Pasien Di Instalasi Rawat Inap Anak RSUD. DR. RM. Djoelham Binjai - Peby Muhammad Ramdhan; Nuraini Nuraini; Ramadhani Syafitri Nst (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Nurses must correctly identify patients as people who will be given certain services or treatment, this must be done by adapting the service or treatment to each patient. This identification process requires at least two ways of identification, such as name, identification number, date of birth, barcoded bracelet or others. The aim of this research is to analyze the behavior of nurses in wearing patient identification bracelets in the children's inpatient installation at RSUD. Dr. RM. Djoelham Binjai. This research uses qualitative research (In-depth interviews). From this research, the sample consisted of 6 (six) people, namely 1 key informant and 5 main informants. The results of the research are that not all nurses know about the Fixed Procedure (PROTAP) for using patient identification bracelets in the class III children's inpatient room at Dr. RSUD. R.M. Djoelham Binjai is good, not all nurses' attitude in carrying out the Permanent Procedure (PROTAP) for wearing patient identification bracelets in the class III children's inpatient room at RSUD Dr. R.M. Djoelham Binjai is not yet good, not all of the nurses' actions were correct in carrying out the Permanent Procedure (PROTAP) for wearing patient identification bracelets in the class III children's inpatient room at Dr. R.M. Joelham Binjai, Suggestions are expected for hospital management to avoid things that are undesirable for babies to also wear identity bracelets, not just mothers. Protap disseminates affirmations and hospital policies that include rewards and punishments for nurses so that there are no mistakes in identity. And continues to provide socialization, education and understanding of the importance of nurse behavior when installing patient identification bracelets in pediatric inpatient rooms.